LATE PLEISTOCENE - HOLOCENE VOLCANISM ON THE KAMCHATKA PENINSULA, NORTHWEST PACIFIC REGION - Ponomareva V.V.; Churikova T.; Melekestsev I.V.; Braitseva O.A.; Pevzner M.; Sulerzhitskii L. (My University, 2007)
Late Pleistocene-Holocene volcanism in Kamchatka results from the subduction of the Pacific Plate under the peninsula and forms three volcanic belts arranged in en echelon manner from southeast to northwest. The cross-arc extent of recent volcanism exceeds 250 km and is one of the widest worldwide. All the belts are dominated by mafic rocks. Eruptives with SiO2>57% constitute ~25% of the most productive Central Kamchatka Depression belt and ~30% of the Eastern volcanic front, but <10% of the least productive Sredinny Range belt. All the Kamchatka volcanic rocks exhibit typical arc-type signatures and are represented by basalt-rhyolite series differing in alkalis. Typical Kamchatka arc basalts display a strong increase in LILE, LREE and HFSE from the front to the back-arc. La/Yb and Nb/Zr increase from the arc front to the back arc while B/Li and As, Sb, B, Cl and S concentrations decrease. The initial mantle source below Kamchatka ranges from N-MORB-like in the volcanic front and Central Kamchatka Depression to more enriched in the back arc. Rocks from the Central Kamchatka Depression range in 87Sr/86Sr ratios from 0.70334 to 0.70366, but have almost constant Nd isotopic ratios (143Nd/144Nd 0.51307–0.51312). This correlates with the highest U/Th ratios in these rocks and suggest the highest fluid-flux in the source region. Holocene large eruptions and eruptive histories of individual Holocene volcanoes have been studied with the help of tephrochronology and 14C dating that permits analysis of time-space patterns of volcanic activity, evolution of the erupted products, and volcanic hazards.
Keywords: 38.37.25 Вулканология; Авачинский; Дикий Гребень; Гамчен; Ильинский; Вулканы Камчатки; Карымский; Кихпиныч; Кизимен; Комарова; Крашенинникова; Ксудач; Безымянный; Малый Семячик; Ключевской